1999
DOI: 10.1182/blood.v93.4.1299
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 (IL-4) and IL-13 Enhance the Effect of IL-1β on Production of IL-1 Receptor Antagonist by Human Primary Hepatocytes and Hepatoma HepG2 Cells: Differential Effect on C-Reactive Protein Production

Abstract: Interleukin-1 receptor antagonist (IL-1Ra) is produced by hepatocytes with characteristics of an acute-phase protein. To examine the role of IL-4 and IL-13 in production of IL-1Ra, human primary hepatocytes and HepG2 human hepatoma cells were cultured in the presence of IL-4 or IL-13 in combination with IL-1β and/or IL-6. The results indicated that both IL-4 and IL-13 amplified the stimulatory effect of IL-1β on production of IL-1Ra protein and messenger RNA (mRNA) by both human primary hepatocytes and HepG2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Synergistic interactions of IL-13 and IL-1β have been previously reported to result in increased eotaxin release and decreased RANTES production in human airway smooth muscle cells (35). Similarly, IL-13 was reported to enhance the stimulatory effect of IL-1β on induction of IL-1 receptor antagonist in human hepatoma HepG2 cells (36). Both IL-13 and IL-1β are detectable in elevated concentrations during the progression of allergic asthma (2,37).…”
Section: Discussionmentioning
confidence: 91%
“…Synergistic interactions of IL-13 and IL-1β have been previously reported to result in increased eotaxin release and decreased RANTES production in human airway smooth muscle cells (35). Similarly, IL-13 was reported to enhance the stimulatory effect of IL-1β on induction of IL-1 receptor antagonist in human hepatoma HepG2 cells (36). Both IL-13 and IL-1β are detectable in elevated concentrations during the progression of allergic asthma (2,37).…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that relaxation can modulate the immune response, for example, by increasing the number of CD4-positive T cells [ 66 ]. These cells are a source of IL-4 that promotes the production of Th2 cytokines and they stimulate the production of IL-1ra from stimulated monocytes and hepatocytes [ 67 ]. One may speculate that this perhaps could be a possible mechanism to the increase of IL-1ra in the active control group.…”
Section: Discussionmentioning
confidence: 99%
“…RNase protection assays. Using an approach recently described for human IL‐1Ra mRNA (17), a riboprobe was created that would distinguish between the 2 major IL‐1Ra mRNA isoforms (sIL‐1Ra and icIL‐1Ra1) as 2 different protected‐size products following RNase treatment. RT‐PCR was performed on total RNA from LPS‐stimulated murine peritoneal macrophages, using a forward primer specific for the icIL‐1Ra1 sequence 5′ IL‐1Ra (GCA‐TGA‐ATT‐CAG‐GGG‐CAG‐TTC‐CAC‐CCT‐GGG‐AAG‐GT) and a reverse primer complementary to the common sequence 3′ IL‐1Ra (GCA‐TAA‐GCT‐TCT‐GGA‐GCT‐TGA‐TAT‐CAT‐CTC‐CAG).…”
Section: Methodsmentioning
confidence: 99%